Emotional Interference in Early Adolescence: Positive Reinforcement Modulates the Behavioral and Neural Effects of Negative Emotional Distracters. (8th December 2019) - Jones, Neil P; Schlund, Michael; Kerestes, Rebecca; Ladouceur, Cecile D
Abstract: Limited research has examined functioning within fronto-limbic systems subserving the resistance to emotional interference in adolescence despite evidence indicating that alterations in these systems are implicated in the developmental trajectories of affective disorders. This study examined the functioning of fronto-limbic systems subserving emotional interference in early adolescence and whether positive reinforcement could modulate these systems to promote resistance to emotional distraction. Fifty healthy early adolescents (10–13 years old) completed an emotional delayed working memory (WM) paradigm in which no distractors (fixation crosshair) and emotional distracters (neutral and negative images) were presented with and without positive reinforcement for correct responses. WM accuracy decreased with negative distracters relative to neutral distracters and no distracters, and activation increased in amygdala and prefrontal cortical (PFC) regions (ventrolateral, dorsomedial, ventromedial, and subgenual anterior cingulate) with negative distracters compared with those with no distracters. Reinforcement improved performance and reduced activation in the amygdala, dorsomedial PFC, and ventrolateral PFC. Decreases in amygdala activation to negative distracters due to reinforcement mediated observed decreases in reaction times. These findings demonstrate that healthy adolescents recruit similar fronto-limbic systems subserving emotional interference as adults and that positive reinforcement can modulate fronto-limbic systems to promote resistance to emotional distraction.